1990
DOI: 10.1007/bf00186465
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of interhemispheric and striate-peristriate connections in visual cortex of the South American marsupial Marmosa elegans (mouse opossum)

Abstract: We have analyzed the distributions of interhemispheric and striate-peristriate connections in the South American marsupial, Marmosa elegans (mouse opossum). Following multiple injections of horseradish peroxidase (HRP) into one hemisphere, we found that anterogradely labeled terminations and retrogradely labeled perikarya are distributed unevenly in the contralateral hemisphere, forming a distinct tangential pattern in striate and peristriate cortex. This pattern delineates as many as eight peristriate areas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Benevento and Ebner (1971) demonstrated V1 projections to these same regions in a n earlier degeneration study, as have Bravo et al (1990) in mouse opossums. These findings suggest that opossums have V1, V2, and at least two other visual areas and that most or all of the cortex between V2 and the somatosensory areas is visual.…”
Section: Visual and Auditory Regionsmentioning
confidence: 79%
See 2 more Smart Citations
“…Benevento and Ebner (1971) demonstrated V1 projections to these same regions in a n earlier degeneration study, as have Bravo et al (1990) in mouse opossums. These findings suggest that opossums have V1, V2, and at least two other visual areas and that most or all of the cortex between V2 and the somatosensory areas is visual.…”
Section: Visual and Auditory Regionsmentioning
confidence: 79%
“…An injection into rostromedial V1 labeled neurons and terminals in several patches in rostral V2. Benevento and Ebner (1971) reported that the rostral striate cortex of opossums projects to the rostral peristriate cortex, whereas the caudal striate cortex projects to the caudal peristriate cortex, a pattern consistent with the concept of V2 (also see Bravo et al, 1990). The V2 region has uneven connections with the visual cortex of the other hemisphere (Granger et al, 1985;Cusick and Kaas, 1986) so that V2 contains a series of ovals of sparse interhemispheric connections separated by narrow zones with dense connections.…”
Section: Visual and Auditory Regionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Neurons in V2 have large receptive fields and a reversal in retinotopy is observed at the V1/V2 boundary [Kahn et al, 2000]. Neuroanatomical studies of cortical connections in short-tailed opossums [Kahn et al, 2000] produced similar results to those from studies of brush-tailed possums [Crewther et al, 1984], South American opossums [Martinich et al, 2000], Virginia opossum [Benevento and Ebner, 1971] and mouse opossums [Bravo et al, 1990]. Namely, connections are observed between V1 and the presumptive location of V2, which is immediately rostrolateral to V1.…”
Section: Discussionmentioning
confidence: 93%
“…Callosal bridges similar to those spanning cat area 18 have been described in marsupials (Benevento and Ebner, 1971;Bravo et al, 1990b), rodents (Cusick and Lund, 1981;Montero, 1984, 1990;Bravo et al, 1990a), and tree shrews (Cusick et al, 1985). At least in marsupials and rodents, bridges across area 18a appear to correspond to borders of extrastriate visual areas (Benevento and Ebner, 1971;Montero, 1984, 1990;Bravo et al, 1990a,b).…”
Section: Normal Catsmentioning
confidence: 90%